Exercise for Neuropathic Pain: A Systematic Review and Expert Consensus - Zhang, Yong-Hui; Hu, Hao-Yu; Xiong, Yuan-Chang; Peng, Changgeng; Hu, Li; Kong, Ya-Zhuo; Wang, Yu-Ling; Guo, Jia-Bao; Bi, Sheng; Li, Tie-Shan; Ao, Li-Juan; Wang, Chu-Huai; et al. (Frontiers in Medicine, 2021)
Background: Neuropathic pain (NP), a severe and disruptive symptom following many diseases, normally restricts patients’ physical functions and leads to anxiety and depression. As an economical and effective therapy, exercise may be helpful in NP management. However, few guidelines and reviews focused on exercise therapy for NP associated with specific diseases. The study aimed to summarize the effectiveness and efficacy of exercise for various diseases with NP supported by evidence, describe expert recommendations for NP from different causes, and inform policymakers of the guidelines. Design: A systematic review and expert consensus. Methods: A systematic search was conducted in PubMed. We included systematic review and meta-analysis, randomized controlled trials (RCTs), which assessed patients with NP. Studies involved exercise intervention and outcome included pain intensity at least. Physiotherapy Evidence Database and the Assessment of Multiple Systematic reviews tool were used to grade the quality assessment of the included RCTs and systematic reviews, respectively. The final grades of recommendation were based on strength of evidence and a consensus discussion of results of Delphi rounds by the Delphi consensus panel including 21 experts from the Chinese Association of Rehabilitation Medicine. Results: Eight systematic reviews and 21 RCTs were included. Exercise, such as strengthening, stretching, aquatic aerobic or balance training, may be beneficial to neuropathic pain relief and functional recovery. Therefore, proper exercise programs can be considered as an effective alternative treatment or complementary therapy for most patients with NP caused by different diseases, including spinal cord injury, stroke, multiple sclerosis, Parkinson’s disease, cervical radiculopathy, sciatica, diabetic neuropathy, chemotherapy-induced peripheral neuropathy, HIV/AIDS, and surgery. Furthermore, there is limited evidence to provide more detailed information about the types, frequency, and intensity of exercise. Conclusions: The consensus statements provided medical staff and policymakers with appliable recommendations for the formulation of exercise prescription for LBP. This consensus statement will require regular updates after five-ten years.